PELAKSANAAN PASAL 155 KOMPILASI HUKUM ISLAM TENTANG KETENTUAN IDDAH BAGI JANDA PUTUS PERKAWINAN KARENA KHULU’ DI KANTOR URUSAN AGAMA KECAMATAN SIMO KABUPATEN BOYOLALI - Zahroh, Siti; Syamsuddin, Syamsuddin; Baehaqi, Baehaqi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2023)
This research is a qualitative research with a descriptive narrative literature approach that takes literature as its source and interviews. The data collection technique in this study is considering that this research uses library research. To analyze the data the writer will do a qualitative analysis. This form of analysis is carried out with explanations, not in the form of statistical figures or other figures. The method used in analyzing this data uses the deductive method, namely